EVALUASI PENERAPAN SISTEM AKUNTANSI DANA KAS KECIL PADA PT. SUNGAI BUDI CIREBON - Amroni, Amroni; Akbari, Safitri; Suwandi, Suwandi; Turini, Turini; Kristiani, Jesica Laura (Fakultas Ekonomi dan Bisnis, 2023)
This research aims to determine petty cash management at PT. Sungai Budi Cirebon Branch and to find out the internal controls applied to the management of petty cash funds at the company. Research conducted at PT. Sungai Budi Cirebon Branch uses a research method related to petty cash funds, namely the imprest fund method. The results of this research are PT. Sungai Budi Cirebon Branch has implemented petty cash fund management (using the imprest fund method) in accordance with applicable accounting standards. This research still has several limitations in the field of internal control, namely cash disbursement transaction documents have not been stamped